2020
DOI: 10.1021/acs.analchem.0c01223
|View full text |Cite
|
Sign up to set email alerts
|

Capture of Electrochemically Generated Fleeting Carbazole Radical Cations and Elucidation of Carbazole Dimerization Mechanism by Mass Spectrometry

Abstract: The capture of reactive intermediates is important for the elucidation of reaction mechanisms. We report the first observation of electrochemically generated, short-lived radical cations of carbazole (t 1/2 ≈ 97 μs) and two N-substituted carbazole derivatives by mass spectrometry. In addition, online investigation of the reactivity of electrochemically generated carbazole radical cations supports that the carbazole dimerization mechanism involves the reaction of one radical cation with one neutral molecule rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…The rotation of the Pt wheel electrode was necessary to form a thin liquid film of electrolyte solution under the impact of high‐flux gas stream of DESI. As the delay time (the time between occurrence of reaction and detection by MS) was on the millisecond order, this device was successful to probe extremely short‐lived intermediates, such as diimine intermediate of a 23 ms half‐life in uric acid oxidation, [67] DMA radical cation DMA + of 0.85–170 μs half‐lives, [68] carbazole radical cations of a 97 μs half‐life, [69] and nitrenium ions in the pathway of 4,4’‐dimethoxydiphenylamine and di‐ p ‐tolylamine oxidation [70] for the first time. The water wheel setup was further simplified using a plane either inclined or flat with carbon paper (Figure 3b) [71] .…”
Section: Electrochemistry In Ms Ion Sourcesmentioning
confidence: 99%
“…The rotation of the Pt wheel electrode was necessary to form a thin liquid film of electrolyte solution under the impact of high‐flux gas stream of DESI. As the delay time (the time between occurrence of reaction and detection by MS) was on the millisecond order, this device was successful to probe extremely short‐lived intermediates, such as diimine intermediate of a 23 ms half‐life in uric acid oxidation, [67] DMA radical cation DMA + of 0.85–170 μs half‐lives, [68] carbazole radical cations of a 97 μs half‐life, [69] and nitrenium ions in the pathway of 4,4’‐dimethoxydiphenylamine and di‐ p ‐tolylamine oxidation [70] for the first time. The water wheel setup was further simplified using a plane either inclined or flat with carbon paper (Figure 3b) [71] .…”
Section: Electrochemistry In Ms Ion Sourcesmentioning
confidence: 99%
“…Thus, ESI is most widely used in EC‐MS to detect the intermediates and products in the liquid electrolyte solutions. [ 19‐22 ] Based on the original ESI technique, several modified EC‐ESI‐MS ionization devices arose, for instance, electrochemical desorption electrospray ionization MS (EC‐DESI‐MS), [ 6,23‐31 ] electrochemical nano‐ESI‐MS (EC‐nESI‐MS), [ 32‐41 ] electrochemical probe electrospray ionization MS (EC‐PESI‐MS), [ 42 ] electrochemical droplet spray ionization mass spectrometry (EC‐DSI‐MS), [ 43‐45 ] and electrochemistry‐neutral reionization‐mass spectrometry (EC‐NR‐MS). [ 46‐47 ] Additionally, to analyze the gases and volatile analytes, DEMS is also widely employed in EC research, especially in electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…21,28−31 Cooks et al reported the successful observation of short-lived intermediates and the evolution of the synthetic reaction during heterogeneous Pd/C-catalyzed hydrogenolysis using inductive ESI-MS (iESI-MS). 21,28 Recently, desorption electrospray ionization (DESI)-MS has been successfully used for electrochemical reactions that occurred in open air, 30,32 enlarging the application of MS for solid surface analysis. Nevertheless, direct and real-time process analysis of reactions in a batch reactor is still a challenge because the current AMS methodology is usually operated under atmospheric (or near atmospheric) pressure, which is far from the typical working conditions of the batch reaction system.…”
mentioning
confidence: 99%
“…The development of classical soft ionization methods like electrospray ionization (ESI) has shown outstanding ability for online monitoring of catalytic reactions that occurred in the liquid phase, which are common in organic synthesis and catalytic reactions . For example, the state-of-the-art online ESI-MS has made great success in real-time monitoring of homogeneous catalytic reactions such as Negishi cross-coupling, Ziegler–Natta polymerization, etc. For heterogeneous catalytic reactions, online MS investigation is still rare, among which the ambient MS (AMS) with a pressured sample infusion (PSI) technique is the most representative. , Cooks et al . reported the successful observation of short-lived intermediates and the evolution of the synthetic reaction during heterogeneous Pd/C-catalyzed hydrogenolysis using inductive ESI-MS (iESI-MS). , Recently, desorption electrospray ionization (DESI)-MS has been successfully used for electrochemical reactions that occurred in open air, , enlarging the application of MS for solid surface analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation